Unveiling the Structural Descriptor of A3B2X9 Perovskite Derivatives toward X‐Ray Detectors with Low Detection Limit and High Stability. (4th May 2020) - Xia, Mengling; Yuan, Jun‐Hui; Niu, Guangda; Du, Xinyuan; Yin, Lixiao; Pan, Weicheng; Luo, Jiajun; Li, Zhigang; Zhao, Hongtao; Xue, Kan‐Hao; Miao, Xiangshui; Tang, Jiang
Abstract: Metal halide perovskites and derivatives exhibit a high sensitivity and low detection limit as direct X‐ray detectors. Inorganic 2D bismuth halide perovskites are promising for X‐ray detections, but have not been reported. Moreover, the quantitative relationship between the structural dimensionality of A3 B2 X9 perovskites and their compositions has never been investigated, and the underlying mechanism is unclear. Here, the key structural descriptors for 2D A3 B2 X9 perovskite derivatives are reported: i) octahedral factor μ, 0.377 < μ < 0895; ii) tolerance factor t, 0.8 < t < 1.06; iii) ( rA ‐0.55)/t < 1.48 Å. Accordingly, a new 2D A3 B2 X9 perovskite derivative, Rb3 Bi2 I9, with high X‐ray attenuation coefficients is found. The assembled X‐ray detector exhibits a high μτ product of 2.51 × 10 −3 cm 2 V −1, good sensitivity for 159.7 μC Gyair −1 cm −2, and a record low detection limit of 8.32 nGyair s −1 among all direct and indirect perovskite X‐ray detectors. The device also exhibits good stability toward external bias and continuous gamma ray radiations (480 000 Gy). This work provides crystal structural insights to rationally design 2D perovskites for new types of radiation detectors. Abstract : The key structural descriptors are reported for 2D A3 B2 X9 perovskite derivatives. By following the above designing rules, Rb3 Bi2 I9 is assembled into an X‐ray detector, exhibiting a low detection limit of 8.32 nGyair s −1 and suppressed ions migration. The inorganic composition also guarantees excellent stability toward continuous radiation from the 60 Co source.